Low Background Radiation Detection Techniques and Mitigation of Radioactive Backgrounds - Laubenstein, Matthias; Lawson, Ian (Frontiers in Physics, 2020)
The study of rare fundamental physics phenomena, such as double-beta decay, rare nuclear decays and dark matter, requires very low levels of background radiation in order to observe a signal. To achieve the required background levels, experiments are located deep underground as these facilities provide significant rock overburden and commensurate reduction in the cosmic ray flux and cosmic ray-spallation induced products. An overview of the sources of these backgrounds will be presented. Taking advantage of the deep underground laboratory spaces, there have been a growing number of underground measurements in other fields, including environmental monitoring, benchmarking of other physical techniques, Life Science studies in low background environments, and material selection. The exceptional sensitivity and high resolution of high-purity germanium detectors allows for very sensitive measurements using gamma-ray spectrometry. Their use has been increasing as they allow for non-destructive measurements of experiment components, which can be directly used if they meet specified background requirements. This paper will discuss the current most sensitive ultra-low background germanium detectors in operation and explain how to achieve the best level of background reduction to attain the best sensitivities. In addition, an overview of several complementary low background measurement methods will be discussed. A proposed program to cross calibrate germanium detectors at several laboratories will be described and a searchable database used to store radioactivity measurements of experimental materials will be introduced.